Körper, Selbst und Melancholie. - Clementi, Siglinde, author.
1 online resource.
Keywords: "This book addresses early modern concepts of the body and the self - focusing on three self-narratives authored by Osvaldo Ercole Trapp (1634-1710), a body description from head to foot, autobiographical writings, and a brief chronicle of the House of Trapp-Caldonazzo. Approaching the complex theme of the question of the early modern self and the historical body, this book intertwines consistent contextualisation and historicisation of self-interpretation and biography. This is done in three steps: first, the content and function of these self-narratives are analysed with reference to current research on early modern self-narratives. In a second step, the life and family history of Osvaldo Ercole Trapp are examined from a microhistorical perspective and placed within the context of the early modern history of Tyrol's nobility. A third step then goes into detail on individual contexts and discourses that refine one's comprehension of these self-narratives: noble masculinity; family, house and line; theories of procreation and education; body experience and body images. It combines textual analysis, historical anthropology with a strong gender-historical perspective, microhistory, and the history of the body as a history of experience and discourse. With this approach, the study makes an innovative contribution to early modern studies on self-narratives, social history of early modern nobility, and to the history of the body as the history of experience and discourse. This volume will be of interest to students and scholars alike interested in intellectual, social and cultural history"--